Hubungan terhadap Kondisi Rambut Mahasiswi Departement Tata Rias dan Kecantikan di Universitas Negeri Padang - Try Syalsabila; Indah Purnama Sari; Siska Miga Dewi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study aims to explore the impact of long-term hijab use on women's hair health. Hair is considered an important part of one's appearance and is often seen as an indicator of physical well-being. The research began after a proposal seminar and was conducted at the Department of Beauty and Cosmetology at Padang State University.Based on existing literature, the use of the hijab can affect hair condition because it covers the head continuously, which may restrict air circulation and increase moisture on the scalp area. Previous studies have shown that women who wear the hijab for more than eight hours a day are at risk of experiencing hair problems such as hair loss, dandruff, and split ends. However, this research also notes that proper hair care can reduce these negative effects, so women who take good care of their hair tend to have healthier hair even while wearing the hijab.The focus of this study is on the general impact of hijab use on hair health, without considering the different hair types of the respondents. The results from observations and interviews emphasize the importance of selecting appropriate hair products to minimize the negative effects of hijab use, supporting the findings of previous studies.